Peran Perempuan Pengerajin Tenun Ikat Dalam Meningkatkan Pendapatan Keluarga Desa Kajowair - Nur Chotimah (FIRM Journal of Management Studies, 2022)
This research was conducted with the aim of looking at the role of women craftsmen of ikat craftsmen in increasing family acceptance and watching the outcrops linking the sites of women artisans in increasing family income in Kajowair Village, Hewokloang District, Sikka Regency. The type of research used is descriptive qualitative research. Data collection was carried out by observation, interviews, documentation. The data analysis technique uses three stages, namely: data reduction, data presentation and conclusion drawing. The results showed that the Role of Ikat Weaving Craftsmen in Kajowair Village in increasing family income was very helpful to fulfill family life. Where weaving can help the husband to earn a living to meet his family's daily needs. But even that is inseparable from the role of a woman as a wife, mother for her children and taking care of the household. As for the weavers, namely: Raw materials that are getting scarce, natural coloring materials that are difficult to obtain, the manufacturing process is complicated in which the dosage of the dye is uncertain so that the results are different and the weather is uncertain, which can hinder the weaving process.Keywords: The Role of Women, Ikat Weaving Craftsmen, Family Income